Prenatal diagnosis of tetralogy of Fallot with an absent pulmonary valve: is this malformation still associated with a poor prognosis? A 5-year single-center experience - Gökhan Bolluk; Süleyman Cemil Oğlak; Özge Özdemir; Helen Bornaun (Perinatal Medicine Foundation, 2023)
Objective: This study sought to assess the prenatal features and clinical outcomes of cases with a fetal diagnosis of tetralogy of Fallot (TOF) with an absent pulmonary valve (APV) at our maternal-fetal medicine unit. Methods: Twelve cases of TOF and APV prenatally diagnosed at Kanuni Sultan Süleyman Training and Research Hospital between 2015 and 2020 were retrospectively reviewed. Prenatal characteristics, additional cardiac and extracardiac anomalies, and postnatal outcomes of the cases were examined. Results: The median gestational age at diagnosis was 22 weeks (range: 18-24 weeks). The absence of ductus arteriosus was found in all cases (100%). Karyotype analysis was performed in 5 cases. A chromosomal abnormality was detected in 3 of these cases (60%); 2 cases with 22q11 microdeletion, and 1 case with trisomy 21. Parents opted for termination of pregnancy in two of these cases; 1 case with 22q11 microdeletion, and 1 case with trisomy 21. Two patients experienced spontaneous intrauterine fetal demise. Finally, 8 live-born fetuses underwent total correction surgery during the postnatal period. Four (33.3%) out of 12 cases survived at the end of the 4-years follow-up period. Conclusion: While TOF with APV cases were predominantly associated with poor prognoses in the past, more promising results have been obtained in recent years in parallel with the developments in surgery and postnatal care. For this reason, we think that the prognosis will be even better in the coming years as the developments in surgical technique and care continue.